THE ROLE OF TEACHERS IN OVERCOMING POST-PANDEMIC LEARNINGLOSS IN ELEMENTARY SCHOOLS - Hanifah Anjarwati; Yes Matheos Lasarus Malaikosa; Budi Sasomo (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This study aims to knowing the teacher role in planning learning to overcome postpandemic learning loss in class 3 SD Negeri Gendol 1, knowing the role of the teaher in overcoming students reading skills due to post pandemic learning loss in class 3 SD Negeri Gendol1, knowing the teacher role as a motivator forpost-pandemic students in class 3 SDNegeri Gendol1.This study use a qualitative method, in which the researcher directly observes the teacher role as a motivator for students, especially in class 3. The data collection process is carried out using 3 techniques, observation, interviews, and documentation. In data analysisactivities consist of 3 paths, data condensation, data presentation and drawing conclusions. After the researcher conducted the research, the researcher could conclude that learning had been carried out online, the use of learning applications during a pandemic, adjusted the curriculumused, the teacher prepare lesson plans, the teacher used interesting learning media, class 3 students had different reading abilities, the teacher carrying out reading habits forstudents, the teacher makes students to be more active in reading during the learning process,and provides library space and books, the teacher gives appreciation to students, as well as the occurrence of good communication between teacher and parents.